As mulheres no cinema de Pedro Almodóvar Caballero e a reinvenção do melodrama hollywoodiano - Canassa, Rosângela Donizete (2018)
The present thesis "Women in the Pedro Almodóvar Caballero’s cinema and the reinvention of Hollywood melodrama" investigates the cinematographic work of the Spanish director and the reinvention of classic Hollywood melodrama as the called woman´s film of Douglas Sirk. The Spanish filmmaker provoked a reconfiguration of the cinematographic genre and with its insights shifts the social role of the woman from its conventional place in the cinema. The research also allows to establish the debate in the field of Psychoanalysis with the formulations of Sigmund Freud, Georges Bataille, Judith Butler, E. Ann Kaplan and Laura Mulvey around the melodramatic personages and their internal conflicts. The melodrama is renewed from its ironic forms and the appropriation of intertextuality, of the dialogue with the own cinema, works of art, literature, music and dance incorporating them to its narratives and imprinting its authorial mark.